POSSIBILITIES OF CAPACITY OF THE RAILWAY LINE 031 IN SECTION PARDUBICE HL. N. – HRADEC KRÁLOVÉ HL. N. (Perner's Contacts, 2015)
The article discusses possibilities of capacity of the single railway line 031, from point of view a busy intersection between two regional centers Pardubice and Hradec Králové. It resolves capacity due to construction of the double-track section between stations Stéblová - Opatovice nad Labem - Pohřebačka as well as the possibility of introducing a completely periodic timetable including possible effects of this measure to the capacity of the track.
Keywords: double-track section, line capacity, periodic timetable